Human Telomerase Reverse Transcriptase as a Therapeutic Target of Dihydroartemisinin for Esophageal Squamous Cancer - Qingrong Li; Qingrong Li; Qingrong Li; Qiang Ma; Qiang Ma; Qiang Ma; Lei Xu; Chuanli Gao; Chuanli Gao; Chuanli Gao; Lihua Yao; Lihua Yao; et al. (Frontiers Media S.A., 2021)
Objective: To elucidate the oncogenic role of human telomerase reverse transcriptase (hTERT) in esophageal squamous cancer and unravel the therapeutic role and molecular mechanism of dihydroartemisinin (DHA) by targeting hTERT.Methods: The expression of hTERT in esophageal squamous cancer and the patients prognosis were analyzed by bioinformatic analysis from TCGA database, and further validated with esophageal squamous cancer tissues in our cohort. The Cell Counting Kit-8 (CCK8) and colony formation assay were used to evaluate the proliferation of esophageal squamous cancer cell lines (Eca109, KYSE150, and TE1) after hTERT overexpression or treated with indicated concentrations of DHA. Transwell migration assay and scratch assay were employed to determine the migration abilities of cancer cells. Fluorescence microscopy and flow cytometry were conducted to measure the intracellular reactive oxygen species (ROS) levels in cancer cells after treated with DHA. Moreover, RT-PCR and Western blot were performed to test the alteration of associated genes on mRNA and protein level in DHA treated esophageal squamous cancer cell lines, respectively. Furthermore, tumor-bearing nude mice were employed to evaluate the anticancer effect of DHA in vivo.Results: We found that hTERT was significantly upregulated in esophageal squamous cancer both from TCGA database and our cohort also. Overexpression of hTERT evidently promoted the proliferation and migration of esophageal squamous cancer cells in vitro. Moreover, DHA could significantly inhibit the proliferation and migration of esophageal cancer cell lines Eca109, KYSE150, and TE1 in vitro, and significantly down-regulate the expression of hTERT on both mRNA and protein level in a time- and dose-dependent manner as well. Further studies showed that DHA could induce intracellular ROS production in esophageal cancer cells and down-regulate SP1 expression, a transcription factor that bound to the promoter region of hTERT gene. Moreover, overexpression of SP1 evidently promoted the proliferation and migration of Eca109 and TE1 cells. Intriguingly, rescue experiments showed that inhibiting ROS by NAC alleviated the downregulation of SP1 and hTERT in cells treated with DHA. Furthermore, overexpression of SP1 or hTERT could attenuate the inhibition effect of DHA on the proliferation and migration of Eca109 cells. In tumor-bearing nude mice model, DHA significantly inhibited the growth of esophageal squamous cancer xenografts, and downregulated the expression of SP1 and hTERT protein, while no side effects were observed from heart, kidney, liver, and lung tissues by HE stain.Conclusion: hTERT plays an oncogenic role in esophageal squamous cancer and might be a therapeutic target of DHA through regulating ROS/SP1 pathway.